The Spondylotic Man in a Barrel - Almeida, Marco (2025)
Man-in-a-barrel syndrome (MBS) is a rare clinical condition in which patients present with bilateral brachial diplegia, with relatively spared strength in the lower limbs. This syndrome is typically attributed to hypoperfusion brain injury rather than spinal pathology. We describe the case of a 75-year-old man who presented with bilateral upper limb paresis. He had had two cardiorespiratory arrests with no documented neurological sequelae a few years before. Imaging tests however showed severe cervical spondylotic myelopathy as the most likely cause. He was not accepted for surgery given the high surgical risk. Despite its rarity, treatable causes of man-in-a barrel syndrome such as cervical compressive myelopathy must be excluded.